Agreement between a partial coherence interferometer and 2 manual keratometers - Bullimore, Mark A; Buehren, Tobias; Bissmann, Wilfried (Journal of cataract and refractive surgery, 2013)
To establish repeatability and validity of a partial coherence interferometry (PCI) device in patients with astigmatism. Industry and university. Observational studies. A prospective study determined the agreement between the IOLMaster 500 PCI device and the Marco 1-position manual keratometer for measurement of mean corneal power, astigmatic power, and axis. Interinstrument and interoperator reproducibility was also assessed. A retrospective study determined the agreement between the PCI device and the Javal 2-position manual keratometer. Repeatability was also assessed. The 95% limits of agreement (LoA) were determined for all comparisons. Comparing the PCI device and the 1-position manual keratometer, the axis was within 5 degrees in 72.1% of eyes; the cylinder power differed by 0.18 diopter (D) (95% LoA, ±0.45 D) and the mean power by 0.33 D (95% LoA, ±0.25 D). Comparing the PCI device and the 2-position manual keratometer, the axis was within 5 degrees in 77.1% of eyes. The mean difference in cylinder power between the 2 instruments was close to zero (95% LoA, ±0.37 D); however, the mean power differed by 0.34 D (95% LoA, ±0.25 D). The repeatability of the PCI device was better than that of both manual keratometers. Agreement between the PCI device and the 2-position manual keratometer for measures of corneal astigmatism and axis was excellent. The 1-position manual keratometer gave slightly lower estimates of corneal astigmatism, although the agreement for axis was excellent. Thus, the PCI device is an appropriate choice for the calculation of toric intraocular lenses. Dr. Bullimore is a consultant to Carl Zeiss Meditec AG and Alcon Surgical, Inc. Drs. Buehren and Bissmann are employees of Carl Zeiss Meditec AG.